2020
DOI: 10.2147/dmso.s268689
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vivo Antidiabetic Activity Evaluation of Aqueous and 80% Methanolic Extracts of Leaves of <em>Thymus schimperi</em> (Lamiaceae) in Alloxan-induced Diabetic Mice</p>

Abstract: Introduction Diabetes mellitus disorder characterized by increase in serum glucose level as a result of change in fat, protein metabolism, and carbohydrate. The aim of the present study was to investigate the effects of the aqueous and hydroalcoholic leaf extract of Thymus. schimperi on blood glucose levels. Methods The aqueous and 80% methanol extracts of T. schimperi leaves were prepared. Swiss albino mice of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Other Thymus species seem to have anti-diabetic potential: T. schimperi Ronniger seems to lower the blood GLU in alloxan-insulted diabetic mice [ 52 ], and T. praecox Opiz restores GLU homeostasis, ameliorates insulin resistance, and improves pancreatic β-cell function in streptozotocin/nicotinamide-induced diabetic rats [ 53 ].…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%
“…Other Thymus species seem to have anti-diabetic potential: T. schimperi Ronniger seems to lower the blood GLU in alloxan-insulted diabetic mice [ 52 ], and T. praecox Opiz restores GLU homeostasis, ameliorates insulin resistance, and improves pancreatic β-cell function in streptozotocin/nicotinamide-induced diabetic rats [ 53 ].…”
Section: Lamiaceae: Bioactive Propertiesmentioning
confidence: 99%
“…Recent studies have shown promising activity of extract of Thymus schimperi Ronniger in animal models of preeclampsia [ 108 ]. This species belongs to the Lamiaceae family, is a representative plant of Ethiopia [ 109 ], and contains mainly essential oil (i.e., β-myrcene, α-terpinene, limonene, α-humulene, p-cymene) [ 110 ]. Various extracts of T. schimperi have shown anti-oxidant potential [ 111 ], anti-hyperglycemic properties [ 109 ], and anti-hypertensive activity [ 112 ].…”
Section: Plant Extracts In Animal Models Of Preeclampsiamentioning
confidence: 99%
“…This species belongs to the Lamiaceae family, is a representative plant of Ethiopia [ 109 ], and contains mainly essential oil (i.e., β-myrcene, α-terpinene, limonene, α-humulene, p-cymene) [ 110 ]. Various extracts of T. schimperi have shown anti-oxidant potential [ 111 ], anti-hyperglycemic properties [ 109 ], and anti-hypertensive activity [ 112 ]. Mergiaw et al [ 108 ] firstly studied the effect of aqueous crude extract from leaves of T. schimperi at doses of 250, 500, and 1000 mg/kg/day administered to rats with preeclampsia induced by L-NAME (50 mg/kg, p.o.).…”
Section: Plant Extracts In Animal Models Of Preeclampsiamentioning
confidence: 99%
“…Ten of the total studies were conducted in the southern nation nationalities region, 9 in Amhara, four in Tigra, 3 in Addis Abab, 3 in Oromia. Seven studies were done in Moringa Stenopetala [7-9, 11, 17, 19, 23], 2 in Aloe megalacantha B [14,25], 2 in Bersama abyssinica Fresen [32,34], 2 in Datura stramonium [12,31], 2 in Thymus schimperi [26,29], and 14 in different plants. Three in vitro studies were conducted on four plants (Terminalia brownie Fresen, Moringa Stenopetala, Aloe megalacantha B, and Aloe monticola R.) (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%